La presunción de inocencia frente a la inferencia razonable (2017)
In Colombia, the fundamental political right of respect for the innocent status of the accused citizen was absent at the level of the higher canon. The Constitution of 1991 overcomes this gap and within the rich and prolific incorporation of rights, was included in the backbone "Fundamental rights and guarantees". It responds to the principle that man is innocent until proven guilty of final criminal conviction, condemning him. In the meantime, it is presumed.